Evaluation of image quality and task performance for a mobile C-arm with a complementary metal–oxide semiconductor detector - Abiola, Godwin O. (J Med Imaging (Bellingham), 2020)
We assessed interventional radiologists’ task-based image quality preferences for two- and three-dimensional images obtained with a complementary metal–oxide semiconductor (CMOS) flat-panel detector versus a hydrogenated amorphous silicon (a-Si:H) flat-panel detector. CMOS and a-Si:H detectors were implemented on identical mobile C-arms to acquire radiographic, fluoroscopic, and cone-beam computed tomography (CBCT) images of cadavers undergoing simulated interventional procedures using low- and high-dose settings. Images from both systems were displayed side by side on calibrated, diagnostic-quality displays, and three interventional radiologists evaluated task performance relevant to each image and ranked their preferences based on visibility of pertinent anatomy and interventional devices. Overall, CMOS images were preferred in fluoroscopy ([Formula: see text]) and CBCT ([Formula: see text]), at low-dose settings ([Formula: see text]), and for tasks associated with high levels of spatial resolution [e.g., fine anatomical details ([Formula: see text]) and assessment of interventional devices ([Formula: see text])]. No significant difference was found for fluoroscopic imaging tasks emphasizing temporal resolution ([Formula: see text]), for radiography tasks ([Formula: see text]), when using high-dose settings ([Formula: see text]), or tasks involving general anatomy ([Formula: see text]). The image quality preferences are consistent with reported technical advantages of CMOS regarding finer pixel size and reduced electronic noise.